(3GdNWW GdJShjbjI aj eLGd GdUfGYGJ GdOhGFjIs - (3Lhf(B, (3djOSJhfs; (3LGfjS eGcdfjjf(B, s ((3GdbGgQI(B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B,s, 2006)
(3jVe GdNWI GdJShjbjI, GdJMdjd GdNGQLj, GdJMdjd GdOGNdj, JMdjd ehGWf GdbhI hGdVYa hGdaQU GdeJGMI hGdJgOjOGJ GdeMJedI, GSJQGJjLjI GdefJL, GSJQGJjLjI GdeHjYGJ hGdJfHD, GdEJUGdGJ hOhQgG aj JfajP GdESJQGJjLjI, HMhK GdJShjb, GdJfajP hGdeQGbHI, cJGHI GdNWI GdJShjbjIs
(3cTGa eUWdMGJ U(B.215s
Keywords: (3GdCOhjI(B- (3JShjbs; (3GdJShjbs